Implementation of a Food Menu Recommendation System at Ndalem Uti Restaurant Using Collaborative Filtering Based on User Preferences - Rhemadanu, Andreas; Susanto, Rudi; Asri, Anindhiasti Ayu Kusuma (Politeknik Negeri Lhokseumawe, 2025)
This study aims to implement a menu recommendation system at Ndalem Uti Restaurant using a Collaborative Filtering approach based on user preferences. The main problem faced is that customers have difficulty choosing the best-selling menu because of the many choices and minimal information regarding the popularity of each menu. To overcome this, the Collaborative Filtering method is used with the User-Based Cosine Similarity calculation to measure the similarity of preferences between users. The test results show that the recommendation accuracy level reaches 96%, including for new users. This system is able to provide more personalized menu recommendations based on customer order history and ratings. This implementation is expected to improve user experience, optimize sales, and be a solution for the development of culinary businesses in the future.